Efficient Fluoride Removal from Aqueous Solution Using Graphene/Ce Composite Supported on Activated Carbon - Patel, Ruchita V.; Bhasin, Chandra P. (Current Nanomaterials, 2023)
Background: More than 260 million people worldwide are affected by excess fluoride (F- > 1.5 mg/L) in their drinking water. Fluorosis of the teeth and skeleton, among other health issues, is caused by it. Objective: The aim of this study is to evaluate the fluoride removal from contaminated water using graphene-based new adsorbent material. Methods: Graphene (G) was prepared by a facile liquid-phase exfoliation method. CeO2 nanoparticles (NPs) were synthesized by the co-precipitation method. G was treated with CeO2 NPs in a probe sonicator to generate G/Ce material in solution. Finally, the impregnation evaporation process synthesized the G/Ce supported on activated carbon composite (G/Ce/AC). Results: FE-SEM analysis shows that the crumpling and scrolling sheets of G, the nanosized spherical shape of CeO2 NPs and a thick layer of nano-sized spherical particles has built up on the surface of graphene in G/Ce/AC composite. After conversion to G/Ce/AC Composite, the specific surface area of graphene was increased from 3.08 to 485.3621 m2/g. The adsorption of fluoride on G/Ce/AC was investigated using batch systems (effects of pH, contact time, adsorbent dosage and the initial fluoride concentration), adsorption isotherm and kinetic studies. The pseudo-second order was the one that best described the kinetic data, while the Langmuir isotherm best described the equilibrium data with a maximum adsorption capacity equal to 27.9 mg/g. Conclusion: Therefore, the results show that the G/Ce/AC composite was well synthesized and has excellent fluoride adsorption capacity compared to other materials already evaluated for this purpose.
Keywords: kinetics